2019
DOI: 10.1111/cid.12760
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Candida species in the subgingival oral biofilm of patients with peri‐implantitis

Abstract: Background:There are no studies that have investigated the presence of Candida species in the subgingival oral biofilm (OB) of patients with peri-implantitis.Purpose: The aim was to assess the presence of Candida species in the subgingival OB of patients with peri-implantitis.Materials and Methods: Individuals with (group A) and without (group B) peri-implantitis were included. Life style related and demographic data were collected using a questionnaire. In both groups, peri-implant plaque-index (PI), bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 34 publications
1
44
1
Order By: Relevance
“…Mucositis and peri-implantitis are infections caused by fungi and bacteria biofilms [23][24][25]. Understanding this biofilm is essential to guide future therapeutic approaches, such as the use of probiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucositis and peri-implantitis are infections caused by fungi and bacteria biofilms [23][24][25]. Understanding this biofilm is essential to guide future therapeutic approaches, such as the use of probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other study designs should consider including relevant bacteria involved with peri-implant infections (i.e. Porphyromonas gingivalis) [8] and hostpathogen interactions of C. albicans [23].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty studies investigated the microbiological profile of endosseous implants. All of these studies were in English and cross‐sectional in design 9,10,16,18,19,22,24–36 . No randomized controlled trials were identified.…”
Section: Microbiological Profilesmentioning
confidence: 99%
“…Four studies used split‐mouth design to compare implants with peri‐implantitis to healthy implant in the same patient 18,22,30,32 The criteria used to diagnose peri‐implantitis were not consistent among studies (Table 1). Pathogen detection methods utilized in the included studies were culture‐dependent methods (Tables 1 and 2), 19,24,25,35,36 Polymerase chain reaction (PCR), 9,10,22,26–31 (Tables 1 and 3); and 16S rRNA gene sequencing surveys (Tables 1 and 4). 16,17,18,32–34 …”
Section: Microbiological Profilesmentioning
confidence: 99%
See 1 more Smart Citation